Penyusunan Program Ngapel oleh Iprahumas Indonesia - Muhamad Handar (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This study aims to determine the preparation of the NGAPEL program implemented by Iprahumas Indonesia. In its realization in accordance with Law no. 14 of 2008 concerning Openness of Public Information, Iprahumas Indonesia as a government public relations officer functions to provide education and information to the public. The research method used is qualitative. The tools used are observation, documentation, interviews, and literature conducted on informants and key informants in Iprahumas Indonesia. The data obtained was immediately compiled and analyzed so that it became a descriptive data. The results obtained are that the NGAPEL live program on IG TV Iprahumas can share information related to many things and information both in the nature of entertainment, information and education whose scope is in the public sphere or the wider community, the topic of conversation is adjusted to the current conditions, neutral and transparent. The conclusion of this study is that the NGAPEL Iprahumas Indonesia program has become a vehicle for information education in the field of public relations in a practical way in implementing the values ​​of the NGAPEL program as Iprahumas Indonesia's vision,